Rational application of targeted therapeutics in mucinous colon/appendix cancers with positive predictive factors. (20th January 2020) - Dilly, Ashokkumar; Honick, Brendon D.; Lee, Yong J.; Bartlett, David L.; Choudry, Haroon A.
Abstract: Molecular‐targeted therapies have demonstrated disappointing results against most advanced solid cancers. This may largey be attributed to irrational drug use against unselected cancers. We investigated the efficacy of dual MEK‐PI3K drug therapy against KRAS mutated mucin 2 (MUC2)‐secreting LS174T cells and patient‐derived ex vivo and in vivo models of KRAS mutated mucinous colon/appendix cancers. These tumors demonstrate unique phenotypic and genotypic features that likely predict sensitivity to this targeted co‐therapy. Co‐treatment with MEK inhibitor (trametinib) and PI3K inhibitor (pictilisib)‐induced synergistic cytotoxicity and intrinsic mitochondrial‐mediated apoptosis in LS174T cells and tumor explants in vitro. Dual drug therapy also induced endoplasmic reticulum stress (ERS)‐associated proteins (GRP78/BiP, ATF4, and CHOP). However, CHOP knock‐down assays demonstrated that mitochondrial‐mediated apoptosis in LS174T cells was not ERS‐dependent. Dual drug therapy also significantly decreased MUC2 expression, MUC2 post‐translational modification (palmitoylation) and secretion in LS174T cells, suggesting a simultaneous cytotoxic and mucin suppressive mechanism of action. We also demonstrated effective mucinous tumor growth suppression in ex vivo epithelial organoid (colonoid) cultures and in in vivo intraperitoneal patient‐derived xenograft models derived from mucinous colon/appendix cancer. These promising preclinical data support a role for dual MEK‐PI3K inhibitor therapy in mucinous colon/appendix cancers. We postulate that mucinous KRAS mutated cancers are especially vulnerable to this co‐treatment based on their unique phenotypic and genotypic characteristics. Abstract : Mucinous KRAS mutated colon/appendix cancers demonstrate unique genotypic and phenotypic characteristics that allow for the rational application of MEK‐PI3K inhibitor therapy. The present study demonstrates that dual MEK‐PI3K inhibitor therapy (trametinib plus pictilisib) reduces mucinous tumor growth in patient‐derived ex vivo and in vivo models of KRAS mutated mucinous colon/appendix cancer.